Analysis of Halal Tourism Marketing Strategy Through Instagram: A Comparative Study of Indonesia, Malaysia, and Thailand Based on SWOT Analysis - Khamsya Muzamil (UIN Mahmud Yunus Batusangkar, 2025)
This research examines halal tourism marketing strategies on Instagram through a comparative analysis of Indonesia, Malaysia, and Thailand. The study employs content analysis and SWOT methodology to evaluate posts from official tourism accounts @wonderfulindonesia, @malaysia.truly.asia, and @tourismthailand during the first half of 2024. Findings reveal distinct strategic approaches across the three nations. Indonesia demonstrates strengths in showcasing natural beauty and cultural heritage through visually compelling content, though it shows inconsistency in specifically promoting halal tourism destinations and facilities. Malaysia excels through integrated marketing that effectively highlights its comprehensive halal infrastructure and Muslim-friendly amenities, supported by strong institutional coordination. Thailand successfully positions itself as an inclusive